THE ROLE OF DIETARY SUPPLEMENTS IN INFLAMMATORY BOWEL DISEASE: A SYSTEMATIC REVIEW - Rossiyah, Nella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Recurrent episodes of gastrointestinal inflammation induced by an inappropriate immune response to gut bacteria characterize inflammatory bowel disease (IBD). The phrase "inflammatory bowel disease" refers to two distinct forms of idiopathic intestinal disease distinguished by their location and degree of gut wall involvement. Although Crohn disease is substantially more common in women than in men, ulcerative colitis appears to be equally common in both sexes. IBD is often frequent in affluent countries and cooler regions. It occurs when an excessively powerful immune response is generated in response to a normal stimulus, such as food or intestinal flora, in individuals who are genetically predisposed to developing the disorder. Diet significantly influences intestinal inflammation. Unbalanced meals can result in dysbiosis, which impairs the immune system of the host. The Mediterranean Diet is renowned for being anti-inflammatory and dysbiosis-preventing. Probiotics, butyrate, phosphatidylcholine, lactoferrin, palmitoylethanolamide, silymarin, and omega 3 should be introduced to the diet of the patient in order to stabilize the intestinal microbial population and reinforce the mucosal barrier, hence preventing or alleviating IBD symptoms. Intestinal inflammation is usually associated with vitamin D levels and gut flora. Constant study has demonstrated their link, therefore the prescription of probiotics and vitamin D is beneficial for IBD patients.